2023
DOI: 10.1136/bmjgh-2022-010556
|View full text |Cite
|
Sign up to set email alerts
|

Family outcome disparities between sexual minority and heterosexual families: a systematic review and meta-analysis

Abstract: BackgroundThe number of children in sexual minority parent families has increased. This systematic review aims to synthesise the evidence of disparities in family outcomes between sexual minority and heterosexual families and to identify specific social risk factors of poor family outcomes.MethodsWe systematically searched PubMed, the Web of Science, Embase, the Cochrane Library and APA PsycNet for original studies that compared family outcomes between sexual minority and heterosexual families. Two reviewers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 74 publications
(283 reference statements)
0
6
0
Order By: Relevance
“…According to Manning et al, children from same-sex parent families fare as well as children living in households with heterosexual parents across a broad spectrum of well-being 71 . Mazrekaj et al showed no discernible difference in behaviour between children raised by same-sex parents and those raised by heterosexual parents 17 , but some studies found that children raised by same-sex parents perform better in certain areas of psychological adjustment than children raised by heterosexual parents 34 . On the contrary, children from blended, foster, adoptive and similar family structures may have behavioural and health problems since they are considered highly vulnerable.…”
Section: Family Structure and The Health Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Manning et al, children from same-sex parent families fare as well as children living in households with heterosexual parents across a broad spectrum of well-being 71 . Mazrekaj et al showed no discernible difference in behaviour between children raised by same-sex parents and those raised by heterosexual parents 17 , but some studies found that children raised by same-sex parents perform better in certain areas of psychological adjustment than children raised by heterosexual parents 34 . On the contrary, children from blended, foster, adoptive and similar family structures may have behavioural and health problems since they are considered highly vulnerable.…”
Section: Family Structure and The Health Of Childrenmentioning
confidence: 99%
“…Some studies have noted that nontraditional family structures can positively affect health. Zhang et al provide that same-sex couples have better mental health and relationship satisfaction than heterosexual couples and that their children also perform significantly better outcomes than children of heterosexual parents in some psychological adjustment domains 34 . It has been observed that families with communal or cooperative structures positively affect both social integration and the general well-being of their members, especially older adults.…”
Section: The Reflects Of Changes In the Family Structure On Healthmentioning
confidence: 99%
“…This reinforcement may lead to children holding biases towards specific gender characteristics, subsequently influencing their interpersonal interactions [ 28 ]. Although some studies have found no significant differences in the outcomes of parenting between same-sex and traditional heterosexual families [ 29 , 30 ]. However, when there is an unequal division of household labor, it might impact children’s evaluations toward gender groups [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current family research examines the specific contributions of mothers, fathers, and other caregivers to child and adolescent development [7]. New family models, including sexual-minority-parent families, are increasing [8] and not all of them may have father figures. The focus on social and biological fathers' (both addressed by the term 'fathers' in this article) involvement in childcare and offspring psychological development has been renewed.…”
Section: Introductionmentioning
confidence: 99%